Influence Of Green Marketing, Service Quality, And Trust On Customer Loyalty At Indonesian Islamic Banks - Aliya Sukirman; Antong Antong; Manwar Suhardi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study examines the impact of Green Marketing, Service Quality, and Trust on customer loyalty at Bank Syariah Indonesia (BSI) in the city of Palopo. Methodology: A quantitative method approach was employed with 172 respondents. Data were collected through questionnaires and analyzed using multiple regression techniques. Results: The study's findings indicate that Green Marketing and service quality have a positive and significant impact on loyalty, while Trust is the most dominant variable in determining customer loyalty. Findings: These findings explain that environmental-based marketing strategies, improved service quality, and strengthening customer trust are important aspects that BSI must enhance. Novelty & Originality: This study offers novelty by examining Green Marketing in the context of Islamic banking in Palopo, a regional setting rarely explored in prior research. Conclusions: Simultaneously, these three variables have proven significant in increasing loyalty, so their consistent application can drive customer retention, strengthen the long-term relationship between the bank and its customers, and enhance the competitiveness of Islamic banking in the city of Palopo. Type of Paper: This paper is an empirical research paper.